PENERAPAN MODEL PEMBELAJARAN OSBORN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN LARUTAN PENYANGGA DI KELAS XI IPA SMA CENDANA PEKANBARU - Belinda Arabella Syafitri; Abdullah Abdullah; Betty Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research aims to knowing improvement of student learning outcomes on the subject of buffer solution in the XI IPA Cendana High School Pekanbaru. This research was an experimental study with a pretest-posttest design. The research was conducted at Cendana High School Pekanbaru. The sample from the research was students in the XI IPA 1 as an experimental class and students in XI IPA 2 as a control class. The experimental class is a class applied the Osborn learning model while the control class is not treated. Data analysis technique used was t-test. Based on the results of data analysis test, tcount> ttable was 3.333> 1.679, the meaning is the application of Osborn learning model could improve student learning outcomes on the subject of buffer solution in the XI IPA Cendana High School Pekanbaru with the category of increasing learning outcomes in the experimental class based on Score (N-Gain) is high, which is 0.73.Key Words: Osborn Learning Model, Learning Outcomes, Buffer Solution